Dragonflies at the UWM Cedar-Sauk Field Station - (:unkn) unknown (My University, 1979)
When visitors and classes utilize the Field Station facilities during the summer months, they seldom fail to notice dragonflies coursing the old fields or hawking mosquitoes over the little ponds. Their beauty and strong powers of flight have long fascinated observers, but few casual on-lookers are aware of the number of species present at the Field Station and the complexity of their behavior and annual cycles. This report will attempt to familiarize the reader with some aspects of the biology of dragonflies, the species of dragonflies present at the UWM Field Station and the times of the year when each species can be found.
Keywords: dragonflies; Odonata; UWM Field Station